Utilização de doses reduzidas da eCG na indução de estro aplicadas pela via submucosa vulvar em ovelhas da raça Santa Inês - Antunes, Karla Dias (2012)
The objectives were to improve the cost effectiveness of the technique of artificial insemination by transcervical fixed time (TAI) in sheep, testing the effect of dose reduction and use of the route submucosis (SMV) in the application of equine chorionic gonadotropin (eCG) on the efficiency of the synchronization protocol and fertility to artificial insemination (AI) and measure the stress level of the sheep as a result of the application of biotech. Were used six groups of twenty animals, where each group received doses of 200, 300 and 400 IU of eCG intramuscularly (IM) and SMV. Estrus was detected and made 48 hours after insemination by transcervical. Of the 120 treated ewes, 87.5% in estrus. The percentage of intra-uterine deposition of semen was 88.3%. Pregnancy rate ranged from 20 to 70% among the treatments, obtaining an average of 46.66%. The mean cortisol results were significant at 1.15, 2.86 and 0.52 μg/dL according to the three collections, being higher after the animal off the rack at the end of IA. The through SMV can be used to implement eCG at doses of 300 and 400 IU induction protocols and synchronizing estrus and ovulation in sheep associated TAI. The dose reduction to 200 IU eCG intramuscularly decreases the costs of maintaining the efficiency of estrus synchronization protocols and TAI showing better pregnancy rate and prolificacy in sheep, but should not be used route SMV. In general the procedures listed by the transcervical AI will cause stress in sheep. Although the technique of transcervical AI cause stress in animals produces satisfactory results in fertility multiparous ewes Santa Ines.